The acceptability of nanocarriers for drug delivery in different contexts of use: perceptions of researchers and research trainees in the field of new technologies - Chenel V (Dove Medical Press, 2015)
Vanessa Chenel,1–4 Patrick Boissy,1–3 Marie-Sol Poirier,1–3 Jean-Pierre Cloarec,3,4 Johane Patenaude1–3 1Interdisciplinary Institute for Technological Innovation (3IT), 2Department of Surgery, Faculty of Medicine and Health Sciences, Université de Sherbrooke, Sherbrooke, QC, Canada; 3Laboratoire Nanotechnologies et Nanosystèmes (LN2), Centre National de la Recherche Scientifique (CNRS), Université de Sherbrooke, Canada; 4Université de Lyon, Institut des Nanotechnologies de Lyon (INL), site École Centrale de Lyon, France Background: Despite marked optimism in the field of nanomedicine about the use of drug-delivery nanocarriers, uncertainties exist concerning nanocarriers’ possible unintended impacts and effects. These uncertainties could affect user acceptance and acceptability. “Acceptance” refers to the intention to put a technology or a device to a specified use. “Acceptability” refers to a value judgment that accounts for acceptance. The objectives of this study were to characterize impact perception, acceptance, and acceptability in relation to drug-delivery nanocarriers in different contexts of use, and to explore relationships among these concepts.Methods: A sample of European and Canadian researchers and graduate research trainees active in the field of new technologies was recruited by targeted email invitation for participation in a web-based questionnaire study. The questionnaire presented scenarios for two contexts of use (lung cancer, seasonal flu) of drug-delivery nanocarriers with two compositions (carbon, synthetic DNA). Respondents’ impact perception, acceptance, and acceptability judgment in relation to each kind of nanocarrier in each context of use were measured with Likert scale questions and scored using categorical values.Results: Two hundred and fourteen researchers and graduate research trainees completed the questionnaire. The results showed that nanocarrier composition influenced impact perception: as compared with the carbon nanocarrier impact perception, the positive impacts of the synthetic DNA nanocarrier were perceived as more significant and more likely to occur than its negative impacts. Composition did not influence acceptance or acceptability. Context of use significantly influenced acceptance and acceptability of both kinds of nanocarriers: researchers were more likely to accept the use of nanocarriers to treat lung cancer than the seasonal flu. The results also showed a significant relationship between acceptance and the perceived usefulness of the treatments.Conclusion: Nanocarrier composition does not appear to influence acceptance or acceptability. On the other hand, the nanocarriers’ perceived usefulness and context of use are both major factors in accounting for acceptance and acceptability. Keywords: acceptance, impact perception, nanomedicine, researchers’ perceptions, ELSI, E3LS